2016
DOI: 10.21276/sjams.2016.4.7.75
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Intravitreal Triamcinolone Acetonide in Diabetic Macular Oedema

Abstract: The study was carried out to evaluate prospectively the efficacy and safety of intravitreal Triamcinolone acetonide (IVTA) injection in Diabetic Macular Oedema (DME). Patient who were diagnosed to have DME were enrolled in the study after obtaining written informed consent and fulfilling the inclusion criteria. They were then subjected to comprehensive eye examination followed by recording of best corrected visual acuity (BCVA) with Snellen chart and obtaining coloured fundus photography and fundus Fluorescein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
0
1
Order By: Relevance
“…Among diabetic retinopathy patients, majority (41%) had proliferative diabetic retinopathy (PDR and unstable PDR included). In contrast to our study in the study by Ahmed et al, the maximum number of cases belonged to nonproliferative diabetic retinopathy group as compared to proliferative diabetic retinopathy [22].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Among diabetic retinopathy patients, majority (41%) had proliferative diabetic retinopathy (PDR and unstable PDR included). In contrast to our study in the study by Ahmed et al, the maximum number of cases belonged to nonproliferative diabetic retinopathy group as compared to proliferative diabetic retinopathy [22].…”
Section: Discussioncontrasting
confidence: 99%
“…The mean age was 58.66±11.21 years and majority of patients (46%) belonged to 46-60 age group. In the study by Ahmed et al, it was seen that majority of patients belonged to the 51-60 age group [22]. Jain et al found that the mean age of the patients was 51.3±15.8 years, which was in concurrence to our study [23].…”
Section: Discussionsupporting
confidence: 92%